Termite risks to houses in Australia - Reid, Alistair (Emerald, 2009)
Purpose: The purpose of the paper is to provide a review of the dangers that termites pose for houses in Australia and to highlight the inadequacies in the existing research for determining the extent, nature and costs of termite attacks on houses. Design/methodology/approach: The classification of Australian termites is discussed and those classifications most problematic for houses are identified. The reasons why subterranean termites pose a significant risk to houses are explained. An overview of seven noteworthy investigations into termite risks to houses is provided, the findings of the investigations are discussed, and conclusions about the adequacy of the investigations are presented. Findings: Much is known about the distribution and habits of the species of termites that are problematic for houses in Australia, but very little research has been conducted into establishing the extent, nature, and costs of termite attacks on houses. Also, the existing research is ad hoc, piecemeal and inadequate for establishing the risks to houses from termite attack. Originality/value: To date there has been limited research into termite risks to houses in Australia. In making a contribution to this area, this paper examines issues related to termite risks in various states and territories.